The International Self-Report Delinquency Study (ISRD3) in the Research Areas of the Białystok School of Criminology - Ewa Guzik-Makaruk; Marta Dąbrowska (Zeszyty Prawnicze)
On March 24, 2017, the Faculty of Law of the University of Białystok entered into a collaboration agreement with the Central Coordinating Team of the International Self-Report Delinquency Study (ISRD). Te Białystok School of Criminology is currently the only Polish representative participating in ISRD3. Te ISRD study addresses a wide range of issues examined by the Białystok School of Criminology, which launched its research work in 1994. The Białystok School of Criminology conducted its contribution to the ISRD3 research project in June 2017, in Białystok and Rzeszów, two Polish cities, regional capitals of their respective voivodeships. Each of these cities has a population of approximately half a million. The survey was conducted among pupils in their sixth year at a Polish primary (elementary) school (i.e. aged 12+) and in their first or second year at a Polish middle school (the 14+-16+ age group). In addition to the standard content prepared by the ISRD3 CCT, respondents filled in a questionnaire with questions intended to identify local levels of risks such as grooming or sexting. The results of the Polish ISRD3 study will help to diagnose various risks and will be compared to the results obtained in other countries participating in the project. The project’s added value will be the opportunity to develop appropriate preventive and educational programs for the schools in Białystok and Rzeszów which took part in the survey